Effect of mechanical properties of Al2O3/(W, Ti)C ceramic tool material on its tribological characterization. (26th November 2021) - Wang, Limei; Shi, Xiaorui; Wang, Bo; Liu, Hanlian; Huang, Chuanzhen; Liu, Xuefei
Abstract: Ceramic cutting tools are mainly used in high-speed dry machining, thus the tool material is in high temperature friction state with the workpiece material during cutting. The tribological characterizations have a direct impact on the cutting performance of the tool. Therefore, tribological characterizations of two kinds of ceramic tool materials with different mechanical properties against hardened steel H13 were compared at the same temperature, one material is Al2 O3 /(W, Ti)C/Ni with Ni (marked as AWTN), another is Al2 O3 /(W, Ti)C without Ni (marked as AWT). Also, the variation of tribological characterizations of AWT ceramic tool material with different temperatures was emphatically investigated. The results showed that the average friction coefficients of AWT and AWTN decreased with the increase of sliding speed under the same load, and the friction coefficient of AWT was lower than that of AWTN. Although AWTN material had better flexural strength and fracture toughness than AWT at ambient temperature, yet better hardness of AWT material both at room temperature and high temperature led to the lower friction coefficient and lower wear rate, indicating that the hardness had a greater impact on the wear of ceramic tool materials. The friction coefficient of AWT decreased with the increase of load and increased with the increase of temperature. The wear mechanism of Al2 O3 /(W, Ti)C ceramic tool material was different at different temperatures. The conclusion of this research had important guiding significance for the selection of cutting tools and cutting parameters in order to improve the machining quality.